DESIGNING THE TIME OF REST AND TAKING IOT-BASED MEDICINE IN HOSPITALS USING STB - Waldemar Banurea; Mutiara Widasari Sitopu; Charla Tri Selda Manik; Ummu Handasah; Muhammad Sukri Habibi Daulay (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study aims to design an Internet of Things (IoT) based rest-time and medication reminder system in hospitals using Set-Top Box (STB). In the context of patient care, proper management of rest time and medication consumption reminders are essential to support the healing process and the patient's health. The system is designed to utilize the STB as a media display of information that patients can access in the inpatient room. The system consists of a reminder module integrated with a mobile application for medical personnel and families, which can set rest schedules and medication reminders according to the patient's needs. Reminders will be displayed visually and auditorially through the STB, ensuring patients don't miss this important time. The research was carried out by simulating conditions in hospitals involving a number of patients. The results of the evaluation showed that this system succeeded in increasing patient adherence in following the treatment schedule by up to 40% and provided positive feedback on the comfort of the treatment process. The design of an IoT-based reminder system using STBs can improve the efficiency of patient care in hospitals. Recommendations for further development include integration with hospital management systems for more comprehensive monitoring.